Electrochemical Determination of Cefotaxime Using Nafion-Graphene Oxide Modified Electrode - Xu, Fan; Wu, Fanghui; Chen, Le; Cai, Zhengyu; Wei, Xianwen (Asian Journal of Chemistry, 2015)
In this work, graphene was activated by oxidizing acid for improving its dispersity and characterized by scanning electron microscopy and Fourier transform infrared spectroscopy. Then direct electrochemistry of cefotaxime was studied by cyclic voltammetry based on composite film consisting of Nafion and oxygen-containing groups functionalized graphene modified glass carbon electrode. The results demonstrated that the Nafion-graphene oxide modified electrode exhibited obviously electrocatalytic oxidation of cefotaxime by lowering the anodic overpotential due to their excellent compatibility, high specific surface area and good conductivity. Under the optimum conditions, a linear dynamic range of 0.5 μM to 100 μM for cefotaxime was obtained in phosephate buffer solution at pH 2.0 with the detection limit of 2.6 × 10-7 M (S/N = 3). Moreover, the modified electrode possessed some advantages such as easy preparation, rapid response, good stability and high reproducibility. The proposed method was applied to determine cefotaxime in pharmaceutical preparations with satisfactory results.